2009
DOI: 10.7863/jum.2009.28.5.603
|View full text |Cite
|
Sign up to set email alerts
|

Utility of Fetal Echocardiography After Normal Cardiac Imaging Findings on Detailed Fetal Anatomic Ultrasonography

Abstract: Objective. The purpose of this study was to assess the utility of fetal echocardiography (FE) after normal fetal cardiac imaging findings during detailed fetal anatomic ultrasonography (FAU). Methods. We conducted a retrospective cohort review of obstetric ultrasonographic studies from November 2001 through July 2005. We identified women with a singleton gestation with increased risk for congenital heart disease who received FAU performed by a maternal-fetal medicine specialist at 16 to 20 weeks' gestation wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 17 publications
2
15
0
Order By: Relevance
“…However, it cannot be overlooked that when Complete cardiac structures are confirmed normal, 50% of those concerning on echocardiogram were false positives with only one of the 10 considered critical. These findings mimic prior studies that demonstrated not only a low detection rate for major CHD on screening fetal echocardiogram with an unremarkable detailed ultrasound, but also a not insignificant false positive rate on echocardiograms . When combining our dataset with those previously reported, only five major/critical CHDs were discovered despite 4237 screening ultrasounds for a detection rate of 0.12% (95% CI, 0.01%‐0.22%) .…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…However, it cannot be overlooked that when Complete cardiac structures are confirmed normal, 50% of those concerning on echocardiogram were false positives with only one of the 10 considered critical. These findings mimic prior studies that demonstrated not only a low detection rate for major CHD on screening fetal echocardiogram with an unremarkable detailed ultrasound, but also a not insignificant false positive rate on echocardiograms . When combining our dataset with those previously reported, only five major/critical CHDs were discovered despite 4237 screening ultrasounds for a detection rate of 0.12% (95% CI, 0.01%‐0.22%) .…”
Section: Discussionsupporting
confidence: 88%
“…Prior to the universal recommendation of implementing views of the outflow tracts, some advocated for universal fetal echocardiography screening due it its high sensitivity for the detection of CHD . However, since the inclusion of the outflow tracts into the detailed ultrasound, some question the role of screening fetal echocardiogram in the presence of a normal cardiac exam on a detailed ultrasound . Although fetal echocardiography improves detection rates over routine anatomical screening, it is technically demanding and expensive .…”
Section: Introductionmentioning
confidence: 99%
“…145,147 In low-and high-risk populations evaluated in university settings in the recent era, anatomic survey that included the 4-chamber view and outflow tracts minimized the need for detailed fetal echocardiogram. 148 It stands to reason that with uniform standards for training and performance, detection rates may improve, 144 with fetal echocardiography being reserved for those expectant women in whom obstetric scanning suggests the possibility of an abnormality.…”
Section: Obstetric Screeningmentioning
confidence: 99%
“…The fetal echocardiographic examinations were performed by an experienced fetal medicine consultant or by a fetal cardiologist. Recent reports have shown that fetal echocardiography may be of limited benefit after normal anatomy scan results have been obtained at an institution where a high volume of sonographic examinations are performed or where the examinations are read by maternal‐fetal medicine specialists …”
Section: Discussionmentioning
confidence: 99%